Fish Community in Different Mangrove Habitat in Banyuurip Ujung Pangkah – Gresik Regency - Rohmawati, Vivi Dwi; Latuconsina, Husain; Zayadi, Hasan (Sangia Research Media and Publishing, 2021)
Mangroves are an important habitat for fish communities, as spawning, growing and foraging areas. This study aims to compare the species composition, presence frequency and structure of fish communities in different mangrove habitats. The research was conducted at Banyuurip Mangrove Center, Ujung Pangkah District, Gresik Regency, East Java, during July-August 2020. Determination of purposive sampling locations based on physical differences in mangrove habitats. Systematic sampling method was used to estimate the number of mangrove species using belt transects. Fish sample collection uses basic gill nets that are placed at high tide in each mangrove habitat. The results showed that the total number of individual mangrove vegetation was 505 from 12 species, the number of species and individual mangrove vegetation differed between habitats, and the highest was found in coastal mangrove habitats. The number of fish was found as many as 181 individuals from 11 species, 10 families and 5 orders. The number and composition of species, families and fish orders differ between mangrove habitats, with the highest number in coastal mangrove habitats. Mozambique tilapia (Oreochromis mossambicus) dominate the estuary mangrove habitat and giant trevally (Caranx sexfasciatus) dominate the coastal mangrove habitat. There are variations in the structure of fish communities between mangrove habitats, the dominance index value of the fish community in the estuary mangrove habitat is higher and in the medium category, while the coastal mangrove habitat is in the low category. On the other hand, the diversity index value of the fish community in the coastal mangrove habitat is in the high category and the estuary mangrove habitat is in the low category.